Optimizing the Four-Wheel Patrol of the Sabhara Unit in Preventing the Crime of Motor Vehicle Theft in the Legal Territory of the Magelang Police - Tahya Cahya Wiguna (Advances in Police Science Research Journal, 2022)
This research was motivated by the case of motor vehicle theft which became a high crime act that occurred in Magelang Regency. The Magelang Police took preventive action to prevent the crime of motor vehicle theft by optimizing the four-wheel patrol carried out by the Magelang Police Sabhara Unit. The purpose of this study is to find out the process carried out by the Sabhara Unit in preventing the crime of motor vehicle theft and the efforts taken to overcome the factors that influence the lack of optimal patrolling. The theories and concepts used in this research are SWOT Analysis Theory, Management Theory, Theft Concept, Optimization Concept, Four Wheel Patrol Concept, and Crime Prevention Theory. This study uses a qualitative approach, with a descriptive analytical research type that seeks to systematically explain the facts about objects and their problems which are supported by the data obtained, as well as data collection techniques by interviewing, observing and reviewing documents. Based on the results of the study, the authors found the fact that there were several things that had not been fulfilled according to the Perkabaharkam No. 4 of 2011 concerning Patrol. There are several factors that influence the unfulfilled optimization of the four-wheeled Sabhara Unit of the Magelang Police, namely internal factors including strengths and weaknesses. Strengths possessed are the availability of Leadership Motivation, the existence of good HTCK between the functions of the Sabhara Unit and other technical functions, and budget support for patrol implementation, experience. Weaknesses are lack of personnel, lack of ability and awareness of members and negative stigma. External factors include opportunities and threats. Opportunities that are owned are community support and good coordination relationships with side agencies and related agencies. The threats they have are public fear and lack of public awareness of Kamtibmas. Based on the results of the study, the authors provide input to the Sabhara Unit of the Magelang Police to increase the number of personnel and carry out patrol management to the maximum.